Pemanfaatan Limbah Gergaji Kayu sebagai Media Tanam Jamur dan Kain Perca untuk Bahan Baku dalam Packaging Fung – Cube - Rika Astuti Kusuma Wardani; Jumiati - -; Dewi Puspita Sari (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Recycle is needed to increase quality of air, water and soil. This research aims to utilize of waste wood saws as mushroom planting media and patchwork to material in packaging the go - green media (Fung - Cube). The research was conducted on March - May 2016. The mushroom planting media utilize waste wood saws mixed sucrose, wheat bran, CaCO3 with a moisture content of 65% and inokulan. Waste wood saws used as formulation mushroom media for maintain form of baglog. Patchwork used material for packaging Fung - Cube. Patchwork sewn or pasted to be accessories on besek. The result showed utilization of waste wood saws and patchwork can reduce two types of wastes simultaneously through Fung - Cube. Go - green materials were used Fung -Cube that expected to support of sustainable development through paradigm changes utilization of waste which pay attention balance of environment.